Ritma nodrošinājums bērna labizjūtai pirmsskolas izglītības iestādē - Veikšāne, Ieva (Latvijas Universitāte, 2015)
Maģistra darba „Ritma nodrošinājums bērna labizjūtai pirmsskolas izglītības iestādē” mērķis - izpētīt ritma nodrošinājumu pirmsskolas izglītības iestādē bērna labizjūtai. Tika noteikti ritma elementi un ritma nosacījumi, kas veicina bērna labizjūtas attīstību pirmsskolas izglītības iestādē. Maģistra darba ietvaros tika veiks gadījuma pētījums Rīgas Valdorfskolas pirmsskolas 4.grupā un kā datu vākša nas metodes izmantota novērošana un eksperta intervija. Tika analizēta zinātniskā un metodiskā literatūra par ritmu pirmsskolas izglītības iestādē. Pētījuma ietvaros tika novērotas 105 dažādas epizodes un 79 no tām liecina par veiksmīgu ritma nodrošinājumu , kas pilnveido bērna labizjūtu pirmsskolas izglītības iestādē. Tika apkopoti pētījumā iegūtie dati un izstrādāti ieteikumi bērna labizjūtas nodrošināšanai pirmsskolas izglītības iestādē.

3 ANNOTATION The aim of the master paper “ The Rhythm of the child’s wellbeing provision in the pre - school education institution” is to explore the ways how the rhythm support contributes to the well being of the child in the pre - school education institution. The elements and conditions of the rhythm were identified that would promote the development of the child’s well being in the pre - school education inst itution. Within the framework of the master thesis a case study was conducted at the 4 th pre - school group of the Waldorf School in Riga using the observation and the expert interview as the methods of the data collection. As well as, scientific and methodical literature on the subject of the usage of rhythm in the pre - school educational institutions was analyzed. During the research and the observation of 105 various episodes of rhythm usage 79 cases were identified that show the successful usage of rhythm in supporting the child’s wellbeing in the pre - school education institution. The research data was collected and the suggestions for the support of child’s well being in the pre - school education institution were developed and presented.
The Rhythm of the Child’s Wellbeing Provision in the Pre - school Education Institution
Keywords: Pedagoģija; Labizjūta; Ritms; Ritma nodrošinājums; Pirmsskolnieks; Ritma elementi